2003
DOI: 10.1002/cncr.11844
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐carbinol induces a G1 cell cycle arrest and inhibits prostate‐specific antigen production in human LNCaP prostate carcinoma cells

Abstract: BACKGROUNDIndole‐3‐carbinol (I3C), a naturally occurring component of Brassica vegetables, such as cabbage, broccoli, and Brussels sprouts, is a promising anticancer agent for certain reproductive tumor cells. The objective of the current study was to characterize the cell cycle effects of I3C in human prostate carcinoma cells.METHODSThe incorporation of [3H]thymidine and flow cytometry of propidium iodide–stained nuclei were used to monitor I3C‐regulated changes in prostate carcinoma cell proliferation and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 36 publications
(26 reference statements)
2
39
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31] Cover and coworkers showed that I3C induces G 1 cell cycle arrest 24 and this arrest correlates with inhibition of the expression of cyclin-dependent kinase 6 (CDK6), inhibition of the endogenous retinoblastoma (Rb) protein phosphorylation, and increases of the p21 and p27 CDK inhibitors (see Table 1). The I3C-induced cell cycle arrest in both ER-positive MCF-7 and ER-negative MDA-MB-231 human breast cancer cells, which demonstrates that this indole can suppress the growth of mammary tumor cells independently of ER signaling.…”
Section: I3c Induces Cell Cycle Arrestmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] Cover and coworkers showed that I3C induces G 1 cell cycle arrest 24 and this arrest correlates with inhibition of the expression of cyclin-dependent kinase 6 (CDK6), inhibition of the endogenous retinoblastoma (Rb) protein phosphorylation, and increases of the p21 and p27 CDK inhibitors (see Table 1). The I3C-induced cell cycle arrest in both ER-positive MCF-7 and ER-negative MDA-MB-231 human breast cancer cells, which demonstrates that this indole can suppress the growth of mammary tumor cells independently of ER signaling.…”
Section: I3c Induces Cell Cycle Arrestmentioning
confidence: 99%
“…The dietary indoles (I3C, DIM) exert anticancer activity by inducing apoptosis (4-6), exert antimetastatic properties (4,10), inhibit angiogenesis gene products (11), and induce cell cycle arrest (7)(8)(9) in G 1 (5,9) through modulation of cyclin-cdk holoenzyme components. These indoles down-regulate cyclin D1 (4,7,12) and its associated cdk4 (7,12) and cdk6 (5,7,9,12) holoenzyme components in mid-G 1 . They also down-regulate cdk2 (9,12) at the G 1 -S checkpoint.…”
mentioning
confidence: 99%
“…These indoles down-regulate cyclin D1 (4,7,12) and its associated cdk4 (7,12) and cdk6 (5,7,9,12) holoenzyme components in mid-G 1 . They also down-regulate cdk2 (9,12) at the G 1 -S checkpoint. These effects, in turn, prevent hyperphosphorylation of the retinoblastoma protein (5), thereby preventing cell cycle progression into S phase.…”
mentioning
confidence: 99%
“…Arresting the cell cycle prior to S phase suggests a common mechanism of the action for AR antagonists [16,17] . A preliminary in vivo study showed that at a daily intraperitoneal dose of 10 mg/kg, isomer 6012-4 significantly inhibited the growth of subcutaneous LNCaP xenografts.…”
Section: Discussionmentioning
confidence: 99%